Pengaruh Ulasan Online, Persepsi Nilai, Dan Jenis Kelamin Terhadap Niat Berlanjut Untuk Menggunakan Kembali Aplikasi Pemesanan Hotel Agoda Di Indonesia - Juliana, Ratna; Millanyani, Heppy (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The rapid development of technology has led to a trend in online hotel reservations through a platform called an online travel agent (OTA), of which Agoda is one. The Indonesian Review survey (2023) found that the percentage of intentions to reuse Agoda was 43%. The study aims to look at the influence of online reviews, value perceptions, and gender on the intention to reuse the Agoda OTA application in Indonesia. Quantitative research methods using non-probability sampling techniques to get a final sample of as many as 400 respondents. Structural Equation Modeling-Partial Least Square (SEM-PLS) data analysis method using SmartPLS 3.0 application. The results show that (1) hedonic value mediates the relationship between quantity and quality of online reviews on continuance intention to use (2) utilitarian value does not mediate the relationship between quantity and quality of online reviews on continuance intention to use (3) gender does not moderate the relationship between quantity and quality of reviews online on both utilitarian and hedonic values